1993
DOI: 10.3109/08977199308991582
|View full text |Cite
|
Sign up to set email alerts
|

Bone Morphogenetic Protein-2 Causes Commitment and Differentiation in C3Hl0T1/2 and 3T3 Cells

Abstract: C3H10T1/2 cells are an established mesenchymal stem cell line which can differentiate into muscle, fat and cartilage cells when treated with azacytidine. Bone morphogenetic protein-2 (BMP-2) caused a dose dependent differentiation of these cells into fat, cartilage and bone cells-low concentrations favoring adipocytes and high concentrations chondrocytes and osteoblasts. The differentiated phenotypes were stable in the absence of BMP-2. Furthermore, the addition of other growth factors during the differentiati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
350
1
2

Year Published

1996
1996
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 481 publications
(365 citation statements)
references
References 38 publications
12
350
1
2
Order By: Relevance
“…This has also been documented in previous studies on a mesenchymal cell line. 21,22 A combination of bone marrow transplantation and application of rhBMP-2 also suggested a synergistic effect on bone healing. 32 This potential of BMP-2-producing BMSC might be the main reason for our favourable results in vivo obtained even with the less efficient liposome-mediated gene transfer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This has also been documented in previous studies on a mesenchymal cell line. 21,22 A combination of bone marrow transplantation and application of rhBMP-2 also suggested a synergistic effect on bone healing. 32 This potential of BMP-2-producing BMSC might be the main reason for our favourable results in vivo obtained even with the less efficient liposome-mediated gene transfer.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that transfection of BMP-2-cDNA into a mesenchymal cell line stimulated the osteogenic pathway via autocrine and paracrine mechanisms in vitro and in vivo. 21,22 In this study, we investigated the transplantation of BMP-2-producing primary rat bone marrow stromal cells (BMSC), modified by either liposomemediated or adenoviral BMP-2 gene transfer, into bone defects in vitro and in vivo and compared the two approaches with respect to the efficacy of bone regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…However, it has also been demonstrated that BMPs have pro‐adipogenic effects 8. For example, BMP2/4 can induce adipocytic lineage commitment of MSCs through activation of p38 Smad/MAPK signalling 9, 10, 11. In addition, other side effects, such as increased cancer risk related to higher BMP doses, have also been reported 12.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al [2] showed that BMP-2 causes differentiation of a multipotential stem cell line into osteoblast-like cells. To discover small molecules that induce BMP-2, Mundy et al [3] examined more than 30,000 compounds from a collection of natural products and tested the effects of compounds on the expression of the BMP-2 gene.…”
Section: Introductionmentioning
confidence: 99%